The Effects of Minimum Quality Standards: Better or Worse Products? - Paolo G. Garella (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
In a duopoly where two firms' products are differentiated both, horizontally and vertically, introduction of a quality standard affects equilibrium quality levels of both firms. The effects, furthermore, depend upon consumers being or not perfectly informed about qualities. Qualities are strategic substitutes and under perfect information only non-innocuous standards, i.e. above the lowest quality in an unregulated equilibrium, change the equilibrium. However, the average quality in the market may go down due to the standard, because the high quality firm will lower its own quality, and total consumers welfare may decrease. Under uncertainty, even innocuous standards, below the lowest unregulated equilibrium quality, may alter the equilibrium quality choices.
Keywords: 330